Lower extremity power during the squat jump with various barbell loads - Jandacka, D.; Uchytil, J.; Farana, R.; Zahradnik, D.; Hamill, J. (Sports Biomechanics, 2014)
The purpose of this study was twofold: (1) to determine the barbell load that maximised the system power as well as the ankle, knee, and hip joint powers during the squat jump, and (2) to compare the system powers computed from two different methods: the centre of mass (COM) method and the barbell method. Seven male throwers were recruited in this study. The system power (COM method) and the ankle, knee, and hip joint powers were determined with the load incrementally set at 0%, 10%, 30%, 50%, 70%, and 90% of one repetition maximum. The largest system power was observed at the load of 30% (p < 0.008) while the largest ankle and knee powers were observed at 70% and 0% (p < 0.05). The barbell method overestimated the system power (p < 0.001) when compared to the COM method. It was concluded that the barbell method could influence load optimisation in squat jump. The optimal barbell load which maximised the system power did not maximise the ankle, knee, or hip power simultaneously.